Turnover Intention among Gen Z Employees: The Influence of Work Stress and Openness to Experience Personality - Karimah, Agam Umara; Al Karim, Chamilul Hikam (Universitas Ahmad Dahlan, 2025)
Generation Z is poised to dominate Indonesia’s workforce and is often described as adaptable, flexible, and open to new experiences. At the same time, this cohort shows comparatively high turnover intention. This study examined the effects of job stress and openness to experience on turnover intention among Gen Z employees. Using a quantitative correlational design, 251 Indonesian Gen Z workers completed the Openness to Experience Scale, Job Stress Scale, and Turnover Intention Scale via an online survey. Multiple linear regression (JAMOVI) indicated that both predictors significantly explained variance in turnover intention, individually and jointly, with job stress exerting the stronger effect. These findings suggest that Gen Z turnover intention is driven primarily by situational pressures rather than dispositional openness. Organizations should prioritize practices that mitigate stress—such as fair recognition, equitable policies, work–life balance, and supportive interpersonal climates—to curb turnover intention in this demographic.